2003
DOI: 10.1101/gad.1108403
|View full text |Cite
|
Sign up to set email alerts
|

Association of the RENT complex with nontranscribed and coding regions of rDNA and a regional requirement for the replication fork block protein Fob1 in rDNA silencing

Abstract: Silencing within the yeast rDNA repeats inhibits hyperrecombination, represses transcription from foreign promoters, and extends replicative life span. rDNA silencing is mediated by a Sir2-containing complex called RENT (regulator of nucleolar silencing and telophase exit). We show that the Net1 (also called Cfi1) and Sir2 subunits of RENT localize primarily to two distinct regions within rDNA: in one of the nontranscribed spacers (NTS1) and around the Pol I promoter, extending into the 35S rRNA coding region.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
322
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(358 citation statements)
references
References 58 publications
(117 reference statements)
34
322
0
Order By: Relevance
“…FOB1 codes for a protein that binds to DNA elements within the rDNA enhancer region defining the so-called replication fork barrier (Kobayashi and Horiuchi 1996). It has been shown that FOB1 is required for regional Pol II silencing in the intergenic spacer region and thus seems to influence local chromatin structure at this locus (Huang and Moazed 2003). Furthermore, it has been reported recently that Pol II can transcribe intergenic spacer DNA from a bidirectional promoter (E-pro) located within IGS1 Kobayashi and Ganley 2005).…”
Section: Discussionmentioning
confidence: 99%
“…FOB1 codes for a protein that binds to DNA elements within the rDNA enhancer region defining the so-called replication fork barrier (Kobayashi and Horiuchi 1996). It has been shown that FOB1 is required for regional Pol II silencing in the intergenic spacer region and thus seems to influence local chromatin structure at this locus (Huang and Moazed 2003). Furthermore, it has been reported recently that Pol II can transcribe intergenic spacer DNA from a bidirectional promoter (E-pro) located within IGS1 Kobayashi and Ganley 2005).…”
Section: Discussionmentioning
confidence: 99%
“…That enrichment at these sites was specific was established by comparison to the control POL1 locus, where no differences were observed between tagged and untagged strains. Recovery of Esa1p from these sites in the rDNA thus demonstrates that Esa1p maps to the site of its effects on silencing, as observed for targeting of Sir2p (Huang and Moazed, 2003).…”
Section: Esa1 Function Within the Rdnamentioning
confidence: 98%
“…That enrichment at these sites was specific was established by comparison to the control POL1 locus, where no differences were observed between tagged and untagged strains. Recovery of Esa1p from these sites in the rDNA thus demonstrates that Esa1p maps to the site of its effects on silencing, as observed for targeting of Sir2p (Huang and Moazed, 2003).Because esa1 mutants affect global levels of histone H4 acetylation , we tested the effect of esa1 mutants on the levels of acetylation in the rDNA at specific lysine residues on histone tails. We performed ChIP analysis using modification specific antisera at the 25S, 5S, and NTS regions within the rDNA, comparing ESA1 and esa1-414 strains at 33°C where both strains have complete viability ( Figure 3C).…”
mentioning
confidence: 99%
“…Taqman assays confirmed an increase in rDNA-Ty1b interactions in the absence of Sir2p ( Figure 4A). Moreover, deletion of the replication fork blocking site protein, Fob1 (Kobayashi, 2003), which is involved in the localization of the Sir2p-containing RENT complex to the ETS2 domain (Huang and Moazed, 2003b), also caused an increase Figure 4A). Intriguingly, deleting either SIR2 or FOB1 reduced the frequency of intra-rDNA repeat interactions ( Figure 4B, C).…”
Section: S 25s Its1 and It2 Rrnas) Mspi Restriction Sites Are Depmentioning
confidence: 99%
“…Intriguingly, the trf4 strain also showed an increase in the frequency of the intrarDNA interactions between the ETS2 domain and 25S rRNA (Figure 6). This is simply explained by the Sir2- (Houseley et al, 2007b; and Fob1 (Huang and Moazed, 2003a)-dependent silencing of RNA polymerase II promoters within and adjacent to the ETS2 domain. In contrast, the removal of the Trf4 protein does not alter the number of E-pro regions that are being transcribed, but rather causes an increase in the number of Epro CUTs by stabilizing those that have already been produced (Houseley et al, 2007b).…”
Section: S 25s Its1 and It2 Rrnas) Mspi Restriction Sites Are Depmentioning
confidence: 99%